4 - Contributing Factors to Poor Service Delivery by Administrative Employees in the Gauteng Public Service in South Africa - Van Antwerpen, Sumei; Ferreira, Edmund (Africa Development, 2021)
This article reports on a study that was conducted among non-managerial administrative employees in the public sector in Gauteng. The researchers attempted to determine the effect of specified job factors on the wellbeing and service delivery of these employees. Poor service delivery in the country triggered the research. The focus was on the opinions of administrative employees as they are often the ones who have to face the public and do the work. Employees were generally satisfied with their job environment and other job factors. However, the practical skills tests revealed a very low level of competency and the lack of typing and keyboard skills seemed to be the main problem. If the problem is not attended to, poor service delivery will probably continue which will result in cost increases, higher frustration levels of the community, and a decrease in foreign investment.